Factors that influence students intention to choose private college / Ezra Mayau - Mayau, Ezra (2014)
The higher educational sector in Malaysia includes public and private tertiary institutions. Malaysian of higher education are facing challenges, since there are growing number of institutions in which the degree of competition among institutions are increasing whether public or private education institutions in line for the development of new colleges and universities, reduced funding from the government, and the obligation to improve education services continuously to encounter the demands of the market. This study was to examine the factors that influence students' intentions to choose private college. The objective of this study was to identify the relationship between the factors that can influences students' intention to further study at private college. A total of 200 questionnaires were distributed to 200 respondents of undergraduate students. This means that this study was to achieve the desired objectives. The results gained from the data using pie charts, tables, and the scale mean for the number and percentage of the features needed for this study. This study is expected to have a positive impact on all parties including the respondent, directly or indirectly.